THE RELATIONSHIP BETWEEN DIAPHRAGMATIC THICKNESS AND PULMONARY FUNCTION IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE: A CROSS SECTIONAL STUDY - Andika Pradana; Amira Permatasari Tarigan; Pandiaman Pandia; Dimas Pangestu; Nanda Andini (Respiratory Science, 2026)
Background: Diaphragm dysfunction plays an important role in the pathophysiology of chronic obstructive pulmonary disease (COPD) and may contribute to respiratory symptoms and functional limitation. Ultrasonographic assessment of diaphragm thickness has emerged as a non-invasive method to evaluate respiratory muscle involvement; however, its relationship with pulmonary function remains unclear. This study aimed to assess diaphragm thickness and its correlation with pulmonary function in patients with COPD. Methods: A cross-sectional study was conducted involving patients with COPD. Demographic and clinical characteristics, including symptom severity based on the modified Medical Research Council (mMRC) scale and GOLD classification, were recorded. Diaphragm thickness was measured using ultrasonography. Pulmonary function was assessed using spirometry, including FEV1/FVC, percent predicted FEV1, and percent predicted FVC. Correlation analyses were performed to evaluate the relationship between diaphragm thickness and pulmonary function parameters. Results: The study population consisted predominantly of older male patients with moderate to very severe airflow limitation. The mean diaphragm thickness was 0.30 ± 0.08. Diaphragm thickness showed a weak negative correlation with FEV1/FVC (r = −0.184, p = 0.201) and weak positive correlations with percent predicted FEV1 (r = 0.188, p = 0.190) and percent predicted FVC (r = 0.168, p = 0.243). None of these correlations were statistically significant. Conclusion: Diaphragm thickness was not significantly associated with spirometric parameters in patients with COPD. These findings suggest that static diaphragm thickness alone may not adequately reflect pulmonary function impairment, highlighting the need for multidimensional assessment of respiratory muscle involvement.